2010
DOI: 10.1016/j.jare.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel using the microwave technique

Abstract: Biodiesel production is worthy of continued study and optimization of production procedures because of its environmentally beneficial attributes and its renewable nature. Non-edible vegetable oils such as Jatropha oil, produced by seed-bearing shrubs, can provide an alternative and do not have competing food uses. However, these oils are characterized by their high free fatty acid contents. Using the conventional transesterification technique for the production of biodiesel is well established. In this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…Previous results showed that application of radio frequency microwave energy offers a fast, easy route to this valuable biofuel with advantages of enhancing the reaction rate and improving the separation process (Hernando et al, 2007;El Sherbiny et al, 2010). In all these attempts conventional alkali homogenous catalysts were employed.…”
Section: Synergy Between Microwave Irradiation and Heterogeneous Catamentioning
confidence: 99%
“…Previous results showed that application of radio frequency microwave energy offers a fast, easy route to this valuable biofuel with advantages of enhancing the reaction rate and improving the separation process (Hernando et al, 2007;El Sherbiny et al, 2010). In all these attempts conventional alkali homogenous catalysts were employed.…”
Section: Synergy Between Microwave Irradiation and Heterogeneous Catamentioning
confidence: 99%
“…Previous results reported in the literature [17] on the effect of catalyst and methanol to oil ratio on biodiesel production suggest that biodiesel with the best properties was obtained using 1 % KOH by weight as the catalyst. Methanolysis with this catalyst produced the best yields and viscosities of the resulting esters.…”
Section: Resultsmentioning
confidence: 94%
“…Since trans-esterification is a relatively slow process, intense mixing is required both because of the relatively high oil viscosity and in order to ensure sufficient interfacial area between the two reactants present in different phases. The optimum operating temperature for this reaction is 65C, which is slightly above the boiling point of methanol (64.7C) [17]. When the reaction temperature exceeds the boiling point of methanol, the methanol will vaporize and form a large number of bubbles which may inhibit the reaction.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Among alcohols is commonly used is methanol for it is cheaper and more reactive than others (Hsiao et al, 2011). been applying microwave to accelerate thereaction as reviewed by authors (El Sherbiny et al, 2010., Tippayawong et al, 2012. The use ofmicrowaveis an alternativetomanufacture ofbiodiesel enhancing the conversion.…”
Section: Introductionmentioning
confidence: 99%